Managing operational risk in banks during times of instability - Sobanova, Jelena; Kudinska, Marina (Serbian Journal of Management, 2024)
Operational risk management for banks is becoming more important every year and getting more crucial during times of instability.  According to the research, most of the banks were not prepared for COVID-19-pandemic and had to review operational risk procedures immediately to secure their businesses in working from home environment. The War in Ukraine nowadays also influenced operational risk management in banks significantly. The aim of the paper is to understand the operational risk management challenges in banks during times of uncertainty, to highlight the operational risk management weaknesses when working remotely during pandemic or other unpredictable circumstances and to find out potential operational risk management solutions for banks. By gathering and analysing survey data from the finance sector's workforce and empirical evidence, the research is aimed to identify the gaps in managing operational risk in banks during times of instability, making the subject current and relevant. Factors influencing operational risk management form the basis of the qualitative method used in this study. The key findings and results are that banks must re-evaluate their business continuity planning strategies and reinforce their remote working policies, to adjust the controls that exist and enhance the processes that don't have any controls at all with the focus on transaction processing
Keywords: bank operational risk; operational risk management